Desmoplastic fibroma: Case report - Morais, Anne Diollina Araújo; Nunes, Carlos Eduardo Nogueira; Sampieri, Marcelo Bonifácio da Silva; Chaves, Filipe Nobre; Oliveira, Denise Hélen Imaculada Pereira de (Journal of Oral Diagnosis, 2021)
Introduction: Desmoplastic fibroma (DF), an intraosseous tumor of myofibroblastic origin, has been characterized as an uncommon neoplasm. Though representing less than 1% of all bone tumors, it presents a locally aggressive character. Objective: The objective of this article is to report a case of DF, focusing on its clinical, radiographic, and histopathological characteristics, and to discuss the morphological criteria for differential diagnosis while comparing with other benign intraosseous tumors. Case report: The present case concerns a female patient, 31 years old, a leucoderma who sought clinical care with the principal complaint being swelling in the mouth. In the extra-oral examination, no asymmetry was observed, but in the tomographic examination, the presence of a mixed-aspect intraosseous lesion with areas of hypo-density and of hyper-density, being multilocular, with evidence of vestibular cortex bone expansion was observed. An excisional biopsy was performed and in view of the histological and immunohistochemical data, a final diagnosis of DF was reached. Conclusion: Because DF is a rare neoplasm presenting histopathological characteristics superimposed on other entities (whether benign and malignant), thorough clinical, radiographic, histopathological, and immunohistochemical examinations are necessary for a correct diagnosis. Due to its aggressiveness and potential for relapse, the correct choice of treatment and of long-term follow-up is extremely important.